HOW DOES A COMPANY PERFORM WHEN IMPLEMENTING IMPORTANT ASPECTS OF SUSTAINABILITY? AND THE MODERATING ROLE OF CORPORATE REPUTATION. - Pranatalindo Simanjuntak; Emi Boki (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to analyze the impact of ESG on company performance as measured by Return On Assets (ROA) and the moderating role of Corporate Reputation. Secondary data used in this study comes from the Bloomberg website and annual reports of companies indexed by Sri-Kehati and listed on the IDX during 2020-2023. The census sampling method was used in the process of selecting research samples which resulted in 33 companies being sampled. Data analysis of this study uses SEM (Structural Equation Modeling) Analysis with SmartPLS. The results of this study show that ESG has a positive and significant impact on company performance and the role of corporate reputation strengthens the influence of ESG on company performance.